Study of aggressive behavior of primary school age children with psychophysical disorders - Slozanska, Hanna; Burakovska, Nataliia (Social work and education, 2023)
The article highlights the categories of children that belong to children with psychophysical developmental disorders and shows their age characteristics. It is noted that these are children aged 6–7 to 10–11 years who have been diagnosed with hearing impairment (deaf, reduced hearing); visual impairment (blind, low vision); intellectual impairment (mentally retarded, delayed mental development); speech disorders; disorders of the musculoskeletal system; a complex form of impairment (mentally retarded blind or deaf; deaf-blind, etc.); emotional and volitional disorders and children with autism. Due to subjective reasons, children of primary school age with disorders of psychophysical development often demonstrate aggressive behavior without understanding its meaning. The nature of this behavior in many cases is determined by their age characteristics. The reasons for such behavior are the influence of both internal and external factors, which are characterized in the article. An analysis of the works of scientists who tried to explain the peculiarities of the development and manifestation of aggressive behavior in children of primary school age with disorders of psychophysical development was carried out. The presence of various assumptions and arguments for the existence of various reasons for the appearance of aggressive behavior in children with disorders of psychophysical development has been confirmed in the scientific literature. However, a lack of scientific publications on researching the levels of aggressive behavior in children of primary school age with disorders of psychophysical development during the period of active hostilities was found. This became the goal of the study, which revealed a high level of aggression in children of this category. In particular, the use of Bassa-Darka, "Non-existent animal" and "Cactus" methods for diagnosing aggressive behavior in children of primary school age with psychophysical developmental disorders made it possible to reveal a pronounced high level of aggression in the respondents. The data obtained as a result of the diagnosis of the level of aggressive behavior in the specified category of children made it necessary to study the specific causes of such behavior and to develop ways and means of correcting the aggressive behavior of elementary school students with psychophysical development disorders.